Flexible, Scalable, and Efficient Targeted Resequencing on a Benchtop Sequencer for Variant Detection in Clinical Practice. Issue 3 (13th March 2015) - De Leeneer, Kim; Hellemans, Jan; Steyaert, Wouter; Lefever, Steve; Vereecke, Inge; Debals, Eveline; Crombez, Brecht; Baetens, Machteld; Van Heetvelde, Mattias; Coppieters, Frauke; Vandesompele, Jo; De Jaegher, Annelies; et al.
ABSTRACT: The release of benchtop next‐generation sequencing (NGS) instruments has paved the way to implement the technology in clinical setting. The need for flexible, qualitative, and cost‐efficient workflows is high. We used singleplex‐PCR for highly efficient target enrichment, allowing us to reach the quality standards set in Sanger sequencing‐based diagnostics. For the library preparation, a modified NexteraXT protocol was used, followed by sequencing on a MiSeq instrument. With an innovative pooling strategy, high flexibility, scalability, and cost‐efficiency were obtained, independent of the availability of commercial kits. The approach was validated for ∼250 genes associated with monogenic disorders. An overall sensitivity (>99%) similar to Sanger sequencing was observed in combination with a positive predictive value of >98%. The distribution of coverage was highly uniform, guaranteeing a minimal number of gaps to be filled with alternative methods. ISO15189‐accreditation was obtained for the workflow. A major asset of the singleplex PCR‐based enrichment is that new targets can be easily implemented. Diagnostic laboratories have validated assays available ensuring that the proposed workflow can easily be adopted. Although our platform was optimized for constitutional variant detection of monogenic disease genes, it is now also used as a model for somatic mutation detection in acquired diseases.